A Cross-Sectional Study of Blood Pressure Difference in Hypertensive Patients - Ferly Yacoline Pailungan; Ayuk Cucuk Iskandar; Najihah Najihah; Ana Damayanti (An Idea Health Journal, 2026)
Background: Hypertension is a major global health challenge due to its rising prevalence and potential for severe complications. This study analyzed differences in blood pressure among hypertensive patients with and without a medication supervisor Methods: A quantitative, non-experimental, cross-sectional study was conducted at PKM “X” in Tarakan City. Medication supervisors were defined as family members who monitored patients' adherence to medication. The sample included 89 hypertensive patients selected through purposive sampling. Data collection involved interviews and direct blood pressure measurements using a calibrated sphygmomanometer. Bivariate analysis was conducted using the unpaired T-test and Mann-Whitney test. Results: The findings indicate a significant association between medication supervision and systolic blood pressure control. Patients with medication supervisors had a significantly lower mean systolic blood pressure (143.0 ± 16.3 mmHg) than those without supervisors (153.7 ± 16.5 mmHg; p = 0.003, α = 0.05). The mean difference was 10.7 mmHg (95% CI: 3.7–17.7), with a medium-to-large effect size (Cohen’s d = 0.65), demonstrating both statistical and clinical significance. No significant difference was observed in diastolic blood pressure between the group with a medication supervisor (85.1 ± 14.3 mmHg) and the group without (85.5 ± 11.2 mmHg, p = 0.322). These results indicate that the presence of a medication supervisor is a key factor in optimizing systolic blood pressure regulation. Conclusion: A significant difference in blood pressure, particularly systolic blood pressure, was observed between hypertensive patients with and without medication supervision.